2019
DOI: 10.1002/jmv.25425
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology and host genetics of norovirus and rotavirus infections in Portuguese elderly living in aged care homes

Abstract: Norovirus (NoV) and rotavirus group A (RVA) are major agents of acute gastroenteritis worldwide. This study aimed to investigate their epidemiological profile in Portuguese elderly living in long‐term care facilities and to assess the host genetic factors mediating infection susceptibility. From November 2013 to June 2015, 636 faecal specimens from 169 elderly, mainly asymptomatic, living in nursing homes in Greater Lisbon and Faro district, Portugal, were collected. NoV and RVA were detected by real‐time poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…A simplified rough estimation of Lewis status in different geographical settings (~7.5%, 20%, and 33% in Europe/North America, Central America/Asia, and Sub-Saharan Africa, respectively). The proportion of Lewis-negatives vary widely between populations [12,15,16,23,[26][27][28]. Lewis-negative individuals are susceptible to P [6] rotavirus infections, and the relative proportion of P [6] rotavirus infections in a population correspond reasonably well to the proportion of Lewis-negatives in that population.…”
Section: Figurementioning
confidence: 83%
See 1 more Smart Citation
“…A simplified rough estimation of Lewis status in different geographical settings (~7.5%, 20%, and 33% in Europe/North America, Central America/Asia, and Sub-Saharan Africa, respectively). The proportion of Lewis-negatives vary widely between populations [12,15,16,23,[26][27][28]. Lewis-negative individuals are susceptible to P [6] rotavirus infections, and the relative proportion of P [6] rotavirus infections in a population correspond reasonably well to the proportion of Lewis-negatives in that population.…”
Section: Figurementioning
confidence: 83%
“…More studies are warranted to understand if and how HBGA phenotype distribution affects rotavirus disease burden at population level. [12,15,16,22,23,[26][27][28]. Studies have suggested that non-secretors have a lower vaccine response but would also be protected against circulating wildtype strains of the same genotypes which predominantly infect secretors.…”
Section: Figurementioning
confidence: 99%
“…Studies have shown that a large percentage of infections caused by norovirus occur in the winter months 18 21 , although other studies did not observe this 22 . We found 63.9% of outbreaks occurred in the winter months, but many outbreaks were also detected in the warmer months, which occurred mainly in places where there is more movement of people, such as hotels and summer camps.…”
Section: Discussionmentioning
confidence: 88%